Slowing the crystallization speed to prepare high-efficiency flexible tin-based perovskite solar cells - Yangyang Wang; Xiegeng Wang; Long Li; Liwen Zhang (Materials Letters: X)
In this study, five hydrochlorides are used as additives to slow the crystallization rate between SnI2 and AI (A+=MA+, FA+, Cs+) to prepare high-quality perovskite films. This study on film morphology, crystallization and non-radiative recombination demonstrates the effects of organic amine cations with different chain lengths on the quality of thin films. A flexible solar cell device with a lead-free perovskite film doped with PACl is also obtained achieving an efficiency of 5.52 %.